Komunikasi dan Konflik dalam Hubungan Romantis - Fauzi, Achmad (PROPAGANDA, 2024)
Communication is a vital element in healthy romantic relationships. This article highlights the role of communication, common types of conflicts in romantic relationships, and effective conflict resolution techniques. The study also examines the influence of technology and attachment styles on communication in romantic relationships. This research uses a literature review method to analyze various aspects of communication in romantic relationships. The results show that effective communication can enhance relationship quality and reduce conflicts. This study provides important insights for couples in managing their relationship dynamics.